TECHNICAL OBSTACLES TO SPEECH INTELLIGIBILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
As voice communication increasingly rely on technological devices, understanding the intricate relationship between equipment properties and communication outcomes becomes imperative. The purpose of this study is to investigate the impact of technical condition of communication equipment on the intelligibility of voice communications. To achieve this goal, methods and results of a qualitative analysis of the voice signals were used, as well as statistical methods for establishing the relevant dependencies. The importance of technical characteristics of voice signals for speech intelligibility was considered. The influence of the technical parameters of electronic communication equipment and the working environment on the technical characteristics of voice signals and thus on the intelligibility of speech was discussed. On the basis of the research, conclusions were drawn highlighting the serious influence of the communication equipment characteristics and the expertise of the service personnel on speech intelligibility.